A METHOD OF COMPUTER SIMULATION MODELING OF USER AND BOT BEHAVIOR IN A RECOMMENDATION SYSTEM USING THE GRAPH DATABASE NEO4J - Yelyzaveta Meleshko; Mykola Yakymenko; Viktor Bosko (Сучасний стан наукових досліджень та технологій в промисловості, 2021)
The subject matter of the article is the process of computer simulation modeling of complex networks. The goal is to develop a method of computer simulation modeling of ordinary user and bot behavior in a recommendation system based on the theory of complex networks to test the accuracy and robustness of various algorithms for generating recommendations. The tasks to be solved are: to develop a computer simulation model of user and bot behavior in a recommendation system with the ability to generate datasets for testing recommendation generation algorithms. The methods used are: graph theory, theory of complex networks, statistics theory, probability theory, methods of object-oriented programming and methods of working with graph databases. Results. A method of computer simulation modeling of users and objects in a recommender system was proposed, which consists of generating the structure of the social graph of a recommender system and simulating user and bot behavior in it. A series of experiments to test the performance of the developed computer simulation model was carried out. During the experiments, working and testing datasets were generated. Based on the working datasets, the preferences of users by the method of collaborative filtering were predicted. Based on testing datasets, the accuracy of prediction predictions was checked. The results of the experiments showed that the jitter of the investigated values of the Precision, Recall and RMSE of prediction predictions in most practical cases confidently fits within the allowable fluctuation limits, and therefore the users' behavior in computer simulation model was not random and it real users' behavior with certain preferences was simulated. This confirms the reliability of the developed computer simulation model of a recommendation system. Conclusions. A method of computer simulation modeling of user and bot behavior in a recommendation system, which allows generating datasets for testing the algorithms for generating recommendations, was proposed. The developed method makes it possible to simulate the behavior of both ordinary users and bots, which makes it possible to create datasets for testing the robustness of recommender systems to information attacks, as well as for testing the effectiveness of methods for detecting and neutralizing botnets. The structure of relations between users and objects of the recommender system was modeled using the theory of complex networks. Information attacks of bots were modeled on the basis of known models of profile-injection attacks on recommender systems.